Exploring the Issue of Parental Burnout with ICT’s: How Do the Parents of Children with Disabilities Feel - Stathopoulou, Agathi; Crokou, Vicky; Drigas, Athanasios (International Journal of Online and Biomedical Engineering (iJOE), 2023)
The purpose of this study was to investigate the level of burnout, depression, anxiety and stress experienced by parents with a child with disabilities in Greece. In particular, the negative emotional state is investigated, as well as the factors that may contribute to the occurrence of parental burnout, anxiety, stress and depression. The ultimate goal of the empirical study is to emphasize the importance of the parental role, with the aim of improving parents’ well-being and the development of their emotional and mental resilience. The sample involved 50 parents with children with disabilities. Data were collected using the online forms of questionnaires Parental Burnout Assessment & Depression Anxiety Stress Scale. The results showed that parents are prone to parental burnout, with the pre-dominant dimension being exhaustion from the parental role. The results showed that parents are prone to increased levels of stress, anxiety and depression, with the stress scale predominating. In addition, a statistically significant difference between the two age groups, with older parents experiencing increased levels of parental burnout, as well as stress, anxiety and depression. Regarding the number of children in the family, a positive correlation was found only in terms of anxiety, as parents with more children seem to experience increased levels of anxiety compared to parents with one child. In conclusion, it seems that there are significant positive correlations among the levels of total parental burnout and its individual dimensions and the levels of stress, anxiety and depression.